Corporate governance and corporate culture: the impact on tax avoidance and corporate social responsibility - Arieftiara, Dianwicaksih; Masripah, Masripah; Widyastuti, Shinta (Serbian Journal of Management, 2025)
This study aims to analyze the reciprocal effect of tax avoidance and Corporate Social Responsibility (CSR) by considering the antecedent influence of Corporate Governance (CG) and Corporate Culture (CC). CG indicators include the independence and activities of the board of commissioners (BC) and the audit committee, while CC is measured using indicators of gender diversity on the executive board and power distance. The sample comprises manufacturing companies listed on the Indonesian Stock Exchange (IDX) for the period 2018–2023, totaling 654 firm years. Using a two-stage linear regression, the study showed no reciprocal effect between tax avoidance and CSR. This research failed to document the effect of CG on tax avoidance; however, it does affect CSR. The results showed that CC affects tax avoidance but not CSR. Three important contributions of this study are: providing literature and empirical evidence on the reciprocal effect between tax avoidance and CSR; developing a more comprehensive measure of CC using secondary data; and adding literature on CC in Indonesia and its effect on tax avoidance behavior and CSR disclosure, where existing literature and empirical evidence are limited.